Addressing the challenge of scholarship and industry currency in vocational education: a pilot. (2nd January 2018) - Everingham, Nancy; McLean, David; Mancini, Jane; Mitton, Amber; Williams, Melanie
Abstract: This paper explores a pilot project in which three VET teachers in an Australian dual-sector university trialled a scholarship framework by undertaking a small ethnographic inquiry into current practices in their respective industries. The framework defined a method for engaging with industry while simultaneously developing VET teacher capability in scholarly practice. The teachers were asked to reflect on their experience of engaging in a scholarly project and how new knowledge has been incorporated into their teaching and curriculum design. The reflections were analysed using the indicators of scholarly quality from the self-same framework, and the key enabling factors and benefits were identified. The claimed success of the pilot is traced primarily to having a framework that provided a logical guide for the planning and execution of the projects and institutional support in the form of mentoring and paid time release.